Dynamic monitoring of minimal residual disease in newly‐diagnosed multiple myeloma. Issue 3 (21st December 2022) - Yang, Peiyu; Xu, Weiling; Liang, Xinyue; Yu, Shanshan; Yi, Xingcheng; Liu, Mengmeng; Tian, Mengru; Yue, Tingting; Zhang, Yingjie; Yan, Yurong; Hu, Zhongli; Guo, Qiang; et al.
Abstract :